Study of Antioxidant Effects of Selenium-Enriched Saccharomyces Boulardii on Staphylococcus Aureus Infection - Azam Dadkhah Tehrani; mahnoosh fatemi; Fereshte Ghandehari (Journal of Kerman University of Medical Sciences, 2020)
Background: The most important strategy of the immune system against pathogens is producing active oxygen intermediates with sidelong consequence of oxidative stress induction in body. Probiotics and selenium have recently been proven to be powerful antioxidants that help boost the immune system. Hence, the aim of this study was to investigate the antioxidant effects of Saccharomyces boulardii and selenium-enriched S. boulardii against oxidative stress induction caused by S. aureus in rats. Methods: A total of 36 rats were divided into 6 groups. A: control group, B: S. boulardii treated group, C: selenium-enriched S. boulardii treated group, D: S. aureus infected group, E: S. aureus infected and S. boulardii treated group and F: S. aureus infected and selenium-enriched S. boulardii treated group. At the end of the treatment period, animals were anesthetized and blood samples were collected to measure blood cell count, their indexes and antioxidant factors. Results: There was no significant difference in red blood cell count and its indexes, hematocrit percentage, hemoglobin concentration and also platelet count among experimental groups. While a significant increase in the number of white blood cells was observed in D and E groups compared to control group, the changes in other groups were not significant. Total antioxidant capacity, glutathione concentration and glutathione peroxidase activity decreased in D and E groups, compared with control group. Decreased glutathione peroxidase activity was significant only in F compared to the control group. Conclusion: it is suggested that S. boulardii in selenium-enriched status has strong antioxidant effect against oxidative stress caused by S. aureus infection.